The Application and Implementation of Exclusive Breast Milk Management Video Tutorial Media to Improve Breastfeeding Mother's Knowledge and Skills at Pmb Yustin Tresnowati: Penerapan Media Video Tutorial Penatalaksanaan Asi Eksklusif untuk Meningkatkan Pengetahuan dan Keterampilan Ibu Menyusui di Pmb Yustin Tresnowati - Ningsih, Listia; Dewi, Adinda Putri Sari; Qomar, Umi Laelatul (Prosiding University Research Colloquium, 2024)
Background: The achievement of exclusive breastfeeding in the Kebumen region, particularly in the sub-district of Rowokele in 2023, was 69.2%. One of the factors contributing to the low exclusive breastfeeding rate among babies under six months of age is the lack of knowledge and skills in breastfeeding, as well as challenges in breast milk production for postpartum mothers during the early days after delivery, often extending beyond three days. The consequences of not providing exclusive breastfeeding until the baby is six months old are impaired child growth and development. Utilizing tutorial video media for the management of exclusive breastfeeding can be a viable solution to enhance mothers' knowledge and skills in breastfeeding, as videos engage both the sense of hearing and sight. This multimedia approach caters to various learning senses in the human body, facilitating a better understanding and retention of the information provided. Objective: To apply Video Tutorial Media for the Management of Exclusive Breastfeeding for postpartum mothers to enhance their Breastfeeding Knowledge and Skills. Methods: This research employed a case study design. Five postpartum mothers who met the inclusion and exclusion criteria participated in the study. Data were collected through observation and documentation. Results: The application was conducted for 14 days, starting 6 hours after giving birth. The participants watched the Video Tutorial on the Management of Exclusive Breastfeeding once daily for 14 days. Following the implementation of the Video Tutorial, there was a significant improvement in Knowledge and Skills related to breastfeeding for all five participants. Prior to the application, their knowledge and skills were categorized as poor. Conclusion: The implementation of video tutorial media for the management of exclusive breastfeeding effectively increased the knowledge and skills of breastfeeding mothers.